KARAKTERISTIK DAN PERMASALAHAN TANAH MARGINAL DARI BATUAN SEDIMEN MASAM DI KALIMANTAN - Nata Suharta (Jurnal Penelitian dan Pengembangan Pertanian, 2010)
Characteristics and problems of marginal soils from acid sedimentary rocks in KalimantanMarginal or suboptimal soils are potential for agricultural development such as food crops, estate crops, and industrial planted forest. These soils have low fertility status and susceptible to erosion. In Kalimantan, the marginal soils cover about 30.15 million ha or 57.22% of the total island area, with the major soils consist of Ultisols, few Oxisols, and Inceptisols. The physical properties of marginal soils from acid sedimentary rock are mostly influenced by the type of parent materials ( sandstone or claystone ) , while the chemical properties showed the similar characteristics indicating acid soil reaction, vary in organic matter, and low in cation exchange capacity, exchangeable bases, base saturation, mineral reserve, as well as P and K potentials, but the Al saturation is high. Agricultural development on these soils, other than the physical and chemical properties, should consider the relief condition. The areas with flat to undulating relief are recommended for perennial or food crops, while the annual or estate crops and industrial planted forest can be developed until the hilly area. Land management such as fertilization to improve nutrient status, liming to increase soil reaction and to decrease Al reactivity, and soil conservation practice were recommended. In this time, most of the marginal soils were utilized for estate crops development, such as oil palm, rubber, pepper, and industrial planted forest, and only a limited area for food crops.Keywords: Marginal soil, acid sedimentary rock, Ultisols, Oxisols, Inceptisols, Kalimantan